2002
DOI: 10.1111/j.1151-2916.2002.tb00183.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity of Platelet‐Filled Polymer Composites

Abstract: Platelet-shaped particles of similar size and shape were investigated as fillers for improving the thermal conductivity of polymer-ceramic composite materials. The conductivities of composites filled with hard, stiff ceramic particles exceeded 3.5 W⅐(m⅐K) ؊1 , or >20 times the conductivity of the polymer matrix, and were shown to be almost independent of the intrinsic filler conductivity range of 33-300 W⅐(m⅐K) ؊1 . In contrast, the thermal conductivity of composites filled with soft, platelet-shaped BN filler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
105
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(109 citation statements)
references
References 21 publications
4
105
0
Order By: Relevance
“…[30,31] In the case of a BN powder and high-density polyethylene (HDPE), Zhou et al observed the improvement from 0.26 to 0.45, 0.76, and 1.02 W m À1 K À1 , respectively, when www.afm-journal.de [30] For the case of multiwalled CNTs, the results strongly correlated with the alignment of the CNTs; the numbers varied from 0.6 to 3.4 W m À1 K À1 for a 20 wt% CNT load, whereas the thermal conductivity for the misoriented CNTs was $0.7 W m À1 K À1 . [30] However, in some reports, remarkable improvements were recorded when a fraction of 70 wt% or more of surface-modified AlN powders were filled into an epoxy.…”
Section: Thermal Conductivity Measurementsmentioning
confidence: 99%
“…[30,31] In the case of a BN powder and high-density polyethylene (HDPE), Zhou et al observed the improvement from 0.26 to 0.45, 0.76, and 1.02 W m À1 K À1 , respectively, when www.afm-journal.de [30] For the case of multiwalled CNTs, the results strongly correlated with the alignment of the CNTs; the numbers varied from 0.6 to 3.4 W m À1 K À1 for a 20 wt% CNT load, whereas the thermal conductivity for the misoriented CNTs was $0.7 W m À1 K À1 . [30] However, in some reports, remarkable improvements were recorded when a fraction of 70 wt% or more of surface-modified AlN powders were filled into an epoxy.…”
Section: Thermal Conductivity Measurementsmentioning
confidence: 99%
“…To overcome this fundamental tradeoff with thermal transport in soft materials, attempts have been made to engineer composites with various fillers (10), including metals (11,12), ceramics (13), carbon fibers (14), and nanomaterials such as carbon nanotubes and graphene (4,15,16). Anisotropic thermal conductivity can arise in composite systems by using 1D fillers such as carbon fibers where thermal transport preferentially occurs along the major dimension of the filler (14).…”
mentioning
confidence: 99%
“…Figure 4 shows the ratio de- ), with respect to the filler particle's length scale. This clearly illustrates that the length scale associated with the filler particles is crucial, and that for small particles the interface resistance dominates, as has been widely acknowledged in the literature [4,18,22,23,45,55,56]. More importantly, Figure 4 shows that the usage of highly conductive fillers, i.e., with thermal conductivity on the order of 1000 W·m -1 ·K -1 would require even larger filler particles before the interface resistance ceases to dominate.…”
Section: Characterization Techniquesmentioning
confidence: 64%
“…The net effect of the interface scales with the filler particle surface area, but the effect that the particle should have on the composite scales with its volume. Thus, for small particles the resistance associated with the surface area dominates, as compared to the resistance associated with its volume [13,22,45,46]. Here, a filler particle with a simple cubic geometry is used as an example to illustrate the point.…”
Section: Characterization Techniquesmentioning
confidence: 99%